SYSTEMATIC REVIEW OF THE EFFECTIVENESS AND SAFETY OF SUBCUTANEOUS SEMAGLUTIDE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND OBESITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness and safety of subcutaneous semaglutide in patients with type 2 diabetes mellitus and obesity.Research methods: A systematic review was conducted in accordance with PRISMA guidelines using three databases PubMed, Embase, and Cochrane. Studies were selected based on predefined eligibility criteria. Screening, data extraction, risk-of-bias assessment, and data synthesis were performed independently by two reviewers.Results: A total of 10 studies were included in the analysis. Subcutaneous semaglutide generally showed a trend toward improvement in HbA1c and body weight, although the magnitude of change varied across studies. Some studies reported reductions in body mass index (BMI) and waist circumference. Evidence on cardiorenal outcomes was limited. The most commonly reported adverse events were gastrointestinal in nature.Conclusion: Available evidence suggests that subcutaneous semaglutide may have favorable effects on glycemic control and weight reduction in patients with type 2 diabetes mellitus and obesity, with an overall acceptable safety profile. Further studies with more rigorous designs and longer follow-up are needed to confirm its long-term effectiveness and safety.
Keywords: semaglutide; type 2 diabetes mellitus; obesity; effectiveness; safety; systematic review.